If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3v + 4v = 0 Combine like terms: 3v + 4v = 7v 7v = 0 Solving 7v = 0 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Divide each side by '7'. v = 0 Simplifying v = 0
| 60x^2+60x-10=55x^2+61x-6 | | 34-4x=3(x+2) | | 5+9-2y=7y+3-2y | | 60+22x=30x | | 5+10=2 | | x+10+x+14=22 | | 3x^2+8x-24x+35= | | -5x-2-6(x+1)=-(2x+7) | | 5timesx=12 | | -0.4285714286h=6 | | 33=9 | | 4v+5v+v= | | 5b+2=-2b+8 | | 26x+72=36x | | Qs=(-9)+3P | | Qs=(-9)+3P | | -4w+24=0 | | 18x+5x=-12x-1 | | (4v+6)(4v-6)=0 | | n+25=39 | | 4y+3y+5= | | 28x+66=33x | | -15x=-6x+3 | | 5q+11=2q+5 | | 5p-11=9p+7 | | 300=-222+a | | 6u-u= | | 0.80x+0.40(150)=0.40(150) | | 36+y=-66 | | 35=21y-7 | | 2x^2-9x+12=0 | | -14=-9z-16 |